Antibiotic Resistance of Campylobacter Species in a Pediatric Cohort Study - Schiaffino, Francesca (Antimicrob Agents Chemother, 2019)
The objective of this study was to determine the phenotypic patterns of antibiotic resistance and the epidemiology of drug-resistant Campylobacter spp. from a low-resource setting. A birth cohort of 303 patients was followed until 5 years of age. Stool samples from asymptomatic children (n = 10,008) and those with diarrhea (n = 3,175) were cultured for Campylobacter. Disk diffusion for ciprofloxacin (CIP), nalidixic acid (NAL), erythromycin (ERY), azithromycin (AZM), tetracycline (TE), gentamicin (GM), ampicillin (AMP), amoxicillin and clavulanic acid (AMC), ceftriaxone (CRO), chloramphenicol (C), and trimethoprim-sulfamethoxazole (TMS) was determined. Antibiotic resistances in Campylobacter jejuni and non-C. jejuni isolates from surveillance and diarrhea samples were compared, and the association between personal macrolide exposure and subsequent occurrence of a macrolide-resistant Campylobacter spp. was assessed. Of 917 Campylobacter isolates, 77.4% of C. jejuni isolates and 79.8% of non-C. jejuni isolates were resistant to ciprofloxacin, while 4.9% of C. jejuni isolates and 24.8% of non-C. jejuni isolates were not susceptible to azithromycin. Of the 303 children, 33.1% had been diagnosed with a Campylobacter strain nonsusceptible to both azithromycin and ciprofloxacin. Personal macrolide exposure did not affect the risk of macrolide-resistant Campylobacter. Amoxicillin and clavulanic acid (94.0%) was one of the antibiotics with the highest rates of susceptibility. There is a high incidence of quinolone- and macrolide-resistant Campylobacter infections in infants under 24 months of age. Given the lack of association between personal exposure to macrolides and a subsequent Campylobacter infection resistant to macrolides, there is a need to evaluate the source of multidrug-resistant (MDR) Campylobacter. This study provides compelling evidence to propose amoxicillin/clavulanic acid as a treatment for campylobacteriosis.